The Implementation of Learning Instrument of Soil Forming Material with Cooperative Model Type of Team Assisted Individualization of Elementary School Students (Journal of Primary Education, 2019)
This study has the purpose of improving the science process skills and cognitive learning outcomes of students after the Team Assisted Individualization (TAI) type of cooperative learning model was applied in forming soil material. The method of this study was experimental research. The instrument of this study was tests and non-tests. The results showed that the cooperative learning model of Team Assisted Individualization (TAI) could improve students' science process skills with the value obtained from the N-gain test of 0.72 (high) in the experimental class 1 and 0.76 (high) in the experimental class 2. The cognitive learning outcomes of students have increased by 0.54 (moderate) in the experimental classes 1 and 2 with the classical completeness of 86.1% and 88.89%. This study concluded that the implementation of the Team Assisted Individualization (TAI) learning model has effectively improved students' science process skills.